Fear, Cultural Anxiety, and Transformation: Horror, Science Fiction, and Fantasy Films Remade - Lukas, Scott A.; Marmysz, John (Lexington Books, 2010)
This collection was inspired by the observation that film remakes offer us the opportunity to revisit important issues, stories, themes, and topics in a manner that is especially relevant and meaningful to contemporary audiences. Like mythic stories that are told again and again in differing ways, film remakes present us with updated perspectives on timeless ideas. While some remakes succeed and others fail aesthetically, they always say something about the culture in which_and for which_they are produced. Contributors explore the ways in which the fears of death, loss of self, and bodily violence have been expressed and then reinterpreted in such films and remakes as Invasion of the Body Snatchers, Night of the Living Dead, and Dawn of the Dead. Films such as Rollerball, The Ring, The Grudge, The Great Yokai Wars, and Insomnia are discussed as well because of their ability to give voice to collective anxieties concerning cultural change, nihilism, and globalization. While opening on a note that emphasizes the compulsion of filmmakers to revisit issues concerning fear and anxiety, this collection ends by using films like Solaris, King Kong, Star Trek, Doom, and Van Helsing to suggest that repeated confrontation with these issues allows the opportunity for creative and positive transformation.